Short-term memory assessment by visual tasks in yoga practitioners and non-yoga practitioners: A comparative study - M, Shilpa; R, Kusuma; Gavisiddaiah, Shobharani (National journal of physiology, pharmacy and pharmacology, 2024)
Background: Memory is the storage of acquired knowledge for later recall. Learning and memory form the basis by which individuals adapt their behavior to their particular external circumstances. Without these mechanisms, it would be impossible for individuals to plan for successful interactions and to intentionally avoid predictably disagreeable circumstances. Yoga unites the individual self with the cosmic consciousness, which can be achieved by pranayama, asanas, and meditation. Aims and Objectives: To compare the short-term memory in yoga practitioners and Non yoga practitioners by visual tasks and to assess by visual tasks, the improvement in short-term memory after applying memory-improving methods in yoga practitioners and non-yoga practitioners. Materials and Methods: 50 female subjects performing yoga at least 5 days a week for the past 3 months with no any morbidities and 50 female subjects as controls with no any morbid illness were selected randomly from the general population for the study. The memory assessment and memory-improving methods were applied as per Washington’s Chudler memory assessments. Results: The present study was conducted in the Department of Physiology at Rajarajeswari Medical College Bengaluru on 50 yoga practitioners and 50 controls aged 20–65 years who volunteered for the study. Short-term memory status by the visual task before and after application of certain memory improvement methods by using four tests i.e. Alphabetical test (six trials), Numerical test (six trials), Words test, and Object test were done and analyzed both for the controls and yoga practitioners. The mean age of controls and yoga practitioners was 37.78 ± 9.83 years and 37.16 ± 9.53 years respectively. There is no significant age difference in between the groups. The P = 0.74 (Student’s unpaired t-test). Short-term memory status in yoga practitioners significantly increased in Alphabetical and Numerical tests in Trials 5 and 6 and also in word and object tests, The P = 0.0001 (analysis of variance test), meanwhile, their short-term memory status were compared before and after the practice of yoga for 3 months. In the present study we found there is increase in the short-term memory of the yoga practitioners when compared to their own memory before and after the practice of yoga. Conclusion: The present study was undertaken to compare the short-term memory status in yoga practitioners and non-yoga practitioners and also to evaluate the use of memory-improving methods to improve the short-term memory in them. On the basis of the study results we can conclude that the short-term memory can be improved by practicing yoga. The study showed an improved memory status when the non-yoga practitioners were compared with yoga practitioners after practicing yoga. The memory-improving methods showed improved memory status in the control group.